SISTEM PEMBAGIAN HARTA WARIS 2:1 ANTARA ANAK LAKI-LAKI DAN ANAK PEREMPUAN (Studi Komperatif Pemikiran Muhammad Syahrur dan M. Quraish Shihab) - Tri Atik Muthmainnah; Lutfan Muntaqo (Hukum Keluarga Islam, 2022)
Islamic inheritance law has been regulated very detailed and systematic. Islamic inheritance law regulates who gives the inheritance and the recipient of the inheritance, and what is inherited by the heir and the parts of each heir in detail. The legal principle in Islamic inheritance does not look at the differences between men. All heirs, both male and female, have the same rights, even though the portion of the rights is different. Because what is emphasized in Islamic inheritance law is balanced justice, not equal justice. This principle often triggers polemics and cannot be separated from criticism, due to discrimination in the division of inheritance between men and women. And what often gets special attention is the division of inheritance 2:1 between sons and daughters. Until finally Muhammad Syahrur and M. Quraish Shihab offered a gender-equitable inheritance law product. This research is a type of library research, namely by conducting a study of two sources including primary data sources and secondary data sources. The data that the writer uses in this thesis uses qualitative data, while in analyzing this research the writer uses descriptive analytic. Based on the analysis carried out, it was concluded that: The distribution of inheritance 2: 1 according to Syahrur and Quraish emphasizes that the share of women is the benchmark for the share of sons. According to Syahrur, the male share is the maximum limit and the female share is the minimum limit in inheritance law, and this share can change according to the surrounding objective conditions. Meanwhile, according to Quraish, the distribution of inheritance in 2: 1 is God's decree that has been adapted to the nature, functions and duties assigned to men and women. The division of the inheritance can change according to the will and agreement of all parties to the heirs, provided that the change in the distribution is not due to Allah's decree which is unfair.